The differences between urban marketing and consumption of vegetables versus staple foods. A case study on snap bean consumption and marketing in Bogota, Colombia - Mulder, M (International Center for Tropical Agriculture, 1988)
An attempt was made to highlight the typical issues concerning vegetables in urban marketing and consumption. A theoretical comparison of vegetables and staple foods was carried out. Then, the typical issues were transposed into hypotheses, which were subsequently investigated. An important issue is the perishability of vegetables; extremely fast distribution, without storage or delay, and big supply and price fluctuations are consequences of this. In the consumption study, consumption levels, criteria for defining quality and defects, preferences, and attitudes were measured, together with several socioeconomic factors. For the preference measurement, a new and fast survey method with photographs was used. Attitudes were measured according to general statements for 5 different vegetable products. Apparently, there were 4 underlying patterns in the attitude statements: favorite, good for health, buying and preparation inconvenience, and heaviness. This information was useful to explain the snap bean consumption level by socioeconomic factors and attitudes. Particularly, the attitude about being good for health proved to be of some importance. In this study, institutional consumption was also taken into account. Information was collected about how restaurants dealt with snap beans in their meal preparations. Regarding urban marketing, an attempt was made to clarify how distribution is done and how marketing is connected to consumption, that is how traders look at quality and quality defects, and which market area they serve. Conclusions were drawn on the hypotheses, further vegetable research, agricultural food policies, and improvement by CIAT. (AS)